Factors affecting Exclusive Breastfeeding At the Jambi City Health Center - Nazrina Safitri; M. Ridwan (International Journal Of Health Science, 2023)
Exclusive breastfeeding is the only good nutrition for the growth and development of babies aged 0-6 months. Based on data from the Central Statistics Agency, exclusive breastfeeding coverage in Jambi Province in 2021 was 71.37%. The achievement of exclusive breastfeeding at the Paal X Health Center in JCity in 2019 was 52.80%, so it is considered that it is still less than the target of the local government. This is due to several factors, namely limited knowledge, attitudes, education, duration of work and the age of the mother, greatly affecting exclusive breastfeeding. This research is a quantitative study with a cross-sectional design. The sample was selected by accidental sampling and obtained by 63 respondents. The data obtained from filling out the questionnaire and interviews were carried out univariate and bivariate analysis with chisquare or Fisher exact tests. The results of the statistical test obtained several variables related to the behavior of exclusive ASi distribution to babies at the Paal X health center in Jambi City are knowledge, attitudes, education, work with a p value of < 0.05. There is no relationship between the age of the mother and exclusive breastfeeding at the Paal x Health Center in Jambi City. Factors related to exclusive breastfeeding behavior at Puskesmas Paal X Jambi City are knowledge, attitudes, education, work. Meanwhile, the age factor is not associated with exclusive breastfeeding.